2008
DOI: 10.1002/jnr.21815
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of acetyl‐L‐carnitine on neuropathic pain and apoptosis: A role for the nicotinic receptor

Abstract: Several pathologies related to nervous tissue alterations are characterized by a chronic pain syndrome defined by persistent or paroxysmal pain independent or dependent on a stimulus. Pathophysiological mechanisms related to neuropathic disease are associated with mitochondrial dysfunctions that lead to an activation of the apoptotic cascade. In a model of peripheral neuropathy obtained by the loose ligation of the rat sciatic nerve, acetyl-L-Carnitine (ALCAR; 100 mg/kg intraperitoneally [i.p.] twice daily for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 39 publications
(52 reference statements)
4
30
0
Order By: Relevance
“…Additionally, they decrease the toxic effects of free fatty acids by facilitating ␤ -oxidation [45] . Furthermore, strong inhibition of apoptosis and mitochondrial membrane permeability by carnitine and its ester derivatives has been reported by some studies [22,27,45,49,51] . In this study, the powerful antiapoptotic properties of AL-CAR might have an additional protective effect on cisplatin-treated kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they decrease the toxic effects of free fatty acids by facilitating ␤ -oxidation [45] . Furthermore, strong inhibition of apoptosis and mitochondrial membrane permeability by carnitine and its ester derivatives has been reported by some studies [22,27,45,49,51] . In this study, the powerful antiapoptotic properties of AL-CAR might have an additional protective effect on cisplatin-treated kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…Nicotinic acetylcholine receptors (nAChRs) have been suggested as potentially important signaling molecules in pain and neuroprotection [7,5,14,18,50]. nAChRs are pentameric ligand-gated ion channels composed of combinations of α and/or β subunits (α1–α10; β1–β4) [1].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports support a role for acetylcholine (ACh) in the inhibition and modulation of the transmission of nociceptive information [38, 39]. It has been demonstrated that the cholinergic system is involved in antinociceptive mechanisms, by (1) the activation of the GABAergic system [40]; (2) Muscarinic receptors (mAChR) mediation on spinal and (3) supraspinal sites [41, 42]; (4) inhibition enhancement of nicotinic receptors in the spinal dorsal horn [43]; (5) peripheral mAChR [44] or by interaction with the opioid system; however, this correlation is still not well elucidated.…”
Section: Discussionmentioning
confidence: 99%